A Systematic Review of Primary Healthcare Services: Evaluating Differences and Similarities Between Developed and Developing Nations - Anwar Alrashed MD; Mohamed, Hany Ramadan (South Eastern European Journal of Public Health, 2024)
Background: Primary healthcare (PHC) systems play a critical role in ensuring equitable and effective healthcare delivery. However, significant disparities exist in the scope and performance of PHC services between developed and developing countries. Understanding these differences is crucial for improving global health outcomes. Objective: This systematic review aims to compare the scope and effectiveness of primary healthcare services across developed and developing countries. It seeks to identify key differences in healthcare delivery, system performance, and governance structures and provide insights into enhancing PHC services. Methods: We conducted a comprehensive search of electronic databases, including PubMed, MEDLINE, and Scopus, and explored grey literature and reports from relevant organizations. Studies were selected based on their comparative data on PHC services in developed and developing countries, published in peer-reviewed journals or reputable sources. Data were extracted on study characteristics, population details, and key outcomes related to service delivery and system performance. Quality assessment was performed using appropriate tools for different study designs. Results: The review identified significant variations in PHC service scope and effectiveness between developed and developing countries. Key findings include differences in healthcare delivery models, governance structures, and system performance metrics. The review highlights both strengths and challenges in various contexts, providing a comparative overview of PHC services. Conclusions: The findings emphasize the need for context-specific strategies to improve PHC services. Recommendations include enhancing coordination and governance, addressing gaps in accountability and transparency, and focusing on scalable interventions. This review provides valuable insights for policymakers and health system planners aiming to optimize PHC services globally.